IMAGE OF A. SOLZHENITSYN IN THE RUSSIAN LITERATURE IN THE END OF THE 20th – BEGINNINGS OF THE 21th CENTURIES - Natalia L. Blishch (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The paper deals with Aleksandr Solzhenitsyn’s image and his literary legacy percepted and reflected in artistic and metaliterary discourse. The works under consideration belong to M. Shishkin, L. Ulitskaya, V. Sorokin, Sasha Sokolov, V. Voinovich, S. Dovlatov, Z. Zinik, A. Sinyavsky, T. Kibirov, B. Kenzheyev, Ya. Satunovsky, M. Palei, I. Yarkevich. Some basic emblematic and life-creating features of the writer’s image are reflected and reinterpreted in different ways in these texts – such as imprisonment, the successful literary debut, worldwide fame, persecution and individual resistance to the political regime, exile, status of a prophet and the triumphant return to Russia. Opposition to “malicious forces” becomes a constant style sign of the writer. Before the exile he is famous for rigid aversion of normative canons of an official socialist realism, in exile – he resists to democratic freedom of occidentophiles. Author’s self-nominations in both books, devoted to these opposition periods, – “the calf” (“The Oak and the Calf”) and “kernel” (“The Kernel Between Two Millstones”), are interesting. These images-symbols connected with national peasant ethymology, are organically entered in writer`s art-historical discourse and emphasize a soul-stirring combination of poetic and peasant’s in its character and stylistics. Many patterns of Solzhenitsyn’s literary fate correspond to those of his great predecessors Dostoevsky and Tolstoy. Hence there are quite a lot of parody variations of this projective images in postmodern fiction of the end of the 20th century. The very image of the writer as a warrior (or a fighter) in the fiction of the beginning of the 21st century undergoes mock transformations. The author argues that literature in contemporary geopolitical circumstances might once more obtain its’ lost authoritative status if new writers would appear – those who would combine Nabokovian artistic style with aspiration for truth and righteous fury against social evil which are the basic features of Solzhenitsyn’s creative works.